ESSENTIAL OILS FROM FAMILY ZINGIBERACEAE FOR ANTIMICROBIAL ACTIVITY- A REVIEW - MRIDULA TRIPATHI; PRIYANKA CHAWLA; RUBY UPADHYAY; SHIVANGI TRIVEDI (International Journal of Pharma and Bio Sciences, 2013)
Multi drug resistant pathogenic bacteria are posing a serious problem for the current world. Thus in the search for novel antibiotics traditional plants have been proved to be potent source for antimicrobial agents. Zingiberaceae family constitutes a vital group of rhizomatous medicinal and aromatic plants characterised by the presence of volatile oils and oleoresins of export value. Since the middle ages, essential oils have been widely used for bactericidal, fungicidal, medicinal and cosmetic applications. The aim of this review article is to elucidate major constituents present in essential oils of some medicinally important plants of Zingiberaceae family and to explain their antimicrobial activities.